Lack of predictive power of plasma lipids or lipoproteins for gestational diabetes mellitus in Japanese women. Issue 6 (20th May 2015) - Iimura, Yuko; Matsuura, Masaaki; Yao, Zemin; Ito, Satoru; Fujiwara, Mutsunori; Yoshitsugu, Michiyasu; Miyauchi, Akito; Hiyoshi, Toru
Abstract Aims/Introduction To determine the diagnostic potential of plasma lipids and apolipoproteins in gestational diabetes mellitus (GDM), we carried out a retrospective cohort study of 1, 161 Japanese women at 20–28 weeks of gestation who underwent a glucose challenge test (GCT). Materials and Methods A total of 1, 161 Japanese women at 20–28 weeks of gestation underwent a GCT. Participants with a positive test (GCT[+]) underwent a subsequent oral glucose tolerance test. Clinical and biochemical parameters were determined and quantification of apolipoproteins (Apo), including ApoB, ApoB48, ApoA‐I and ApoC‐III, was carried out. Results The prevalence of GCT(+; with a 130 mg/dL glucose cut‐off) and GDM was 20% and 4%, respectively. There was a trend for increased triglycerides and ApoC‐III in GDM(+) participants. However, the difference in plasma triglycerides, ApoC‐III or ApoB48 did not reach statistical significance between GDM(+) and GDM(−) women. Values of 1‐h glucose (P < 0.001) and fasting glucose (P = 0.002) were significant risk factors for GDM. Conclusions Prediction of GDM using only the ApoC‐III value is not easy, although triglycerides and ApoC‐III were higher in the GDM(+) group. The present findings show no significant difference in plasma lipid levels between women diagnosed with GDM and those with normal glucose tolerance.